1996
DOI: 10.1099/0022-1317-77-4-631
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virus-expressed bovine ephemeral fever virus G but not GNS glycoprotein induces neutralizing antibodies and protects against experimental infection

Abstract: Two related glycoproteins (G and GNs ) encoded in the bovine ephemeral fever virus (BEFV) genome were expressed from recombinant vaccinia viruses (rVV). Both proteins were detected in lysates of rVV-infected cells by labelling with D-[6-3H]glucosamine or by immuno-blotting. The recombinant G protein (mol. mass 79 kDa) appeared slightly smaller than the native G protein but reacted with monoclonal antibodies directed against all defined neutralizing antigenic sites (G1, G2, G3a, G3b and G4). The recombinant G~s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 14 publications
3
43
0
Order By: Relevance
“…Johal et al (2008) showed that the expressed BEFV glycoprotein G by recombinant baculoviruses reacted with BEFV-neutralising monoclonal antibodies (MAbs) to all continuous and conformational antigenic sites and may be a useful vaccine antigen. Vaccinated rabbits and cattle with recombinant vaccinia viruses expressing the glycoprotein G developed high level of antibodies which neutralised BEFV in either mammalian or insect cells (Uren et al, 1994;Hertig et al, 1996). In addition, neutralising G protein monoclonal antibodies injected intraperitoneally conferred passive protection against intracerebral infection of suckling mice (Cybinski et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Johal et al (2008) showed that the expressed BEFV glycoprotein G by recombinant baculoviruses reacted with BEFV-neutralising monoclonal antibodies (MAbs) to all continuous and conformational antigenic sites and may be a useful vaccine antigen. Vaccinated rabbits and cattle with recombinant vaccinia viruses expressing the glycoprotein G developed high level of antibodies which neutralised BEFV in either mammalian or insect cells (Uren et al, 1994;Hertig et al, 1996). In addition, neutralising G protein monoclonal antibodies injected intraperitoneally conferred passive protection against intracerebral infection of suckling mice (Cybinski et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The 81 kDa BEFV G protein is a class I transmembrane glycoprotein which contains typespecific and neutralizing antigenic sites (Cybinski et al, 1990) and induces protective immunity in cattle (Uren et al, 1994 ;Hertig et al, 1996). BEFV and other ephemeroviruses also encode a second non-structural glycoprotein (G NS ) and several other small polypeptides (Walker et al, 1992 ;Wang & Walker, 1993 ;Wang et al, 1994 ;McWilliam et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…BEFV and other ephemeroviruses also encode a second non-structural glycoprotein (G NS ) and several other small polypeptides (Walker et al, 1992 ;Wang & Walker, 1993 ;Wang et al, 1994 ;McWilliam et al, 1997). The G NS glycoprotein is also a class I transmembrane glycoprotein which is structurally related to the G protein but has not been detected in virions and does not induce a neutralizing or protective immune response (Walker et al, 1991(Walker et al, , 1992Hertig et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The vaccinia virus has a large number of genes which can be deleted without preventing replication in cell cultures and, in many cases, the deletion mutant has reduced virulence in animal models [18,77]. These genes have been applied as insertion sites for expression of foreign antigens and genes derived from a variety of pathogens have been stably introduced into the virus, providing potential recombinant vaccines for both veterinary and human applications, for example, genes from hepatitis B virus [76], human immunodeficiency virus (HIV) [18,129], HSV-1 [18], simian immunodeficiency virus [40], FIV [100], rabies virus [8], rinderpest virus [32], PRV [12], bovine ephemeral fever virus [36], and rabbit haemorrhagic disease virus [7]. Both humoral and cellular immune responses to the expression products from these recombinant vaccinia viruses have been demonstrated in animals and humans and, in many cases, their protective immunities have been induced in challenge studies.…”
Section: Recombinant Vaccinia Viruses 1 Vaccinia Virus Vectormentioning
confidence: 99%